Potential mouse models of coronavirus-related immune injury - Nan, Fu-Yao; Wu, Cai-Jun; Su, Jia-Hui; Ma, Lin-Qin (Frontiers in Immunology, 2022)
Basic research for prevention and treatment of coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), continues worldwide. However, owing to the strong infectivity of SARS-CoV-2 and the high mortality rate, it is difficult to carry out relevant research in humans. Here, we reviewed animal models, specifically mice with coronavirus-related lung injury, considering aspects of coronavirus replacement, spike protein, and gene fragments. Appropriate mouse models for evaluating the efficacy of vaccines and treatments for coronavirus-related lung injury were evaluated. COVID-19 is a complex disease and animal models cannot comprehensively summarise the disease process. The application of genetic technology may change this status.